Peripheral (Non)Polishnesses. Museums, Creeping Conflicts, and Transformative Frictions - Kobielska, Maria; Siewior, Kinga (Acta Poloniae Historica, 2024)
Whilst Poland appears today as a paradigmatic example of a homogeneous, exclusive national and cultural identity, reinforced by the hegemonic historical policy of a semi-authoritarian state, it is also challenged by Polish minority histories (civilian, multi-ethnic, non-Catholic, women). The main concern of the present article is the plural ‘Polishness’ that emerges from the constellation of these non-default histories. To examine the frictions of historical narratives in action, authors use spaces of historical museums as a field of observation, perceiving them as memory agents fostering not only confrontational but also negotiative memory politics. To identify situations in which tensions between the ‘central’ Polishness and its unorthodox variants are particularly evident, the paper takes a look at ‘non-central’ Polish territories i.e. ‘post-German’ areas, characterized by a complex heterogeneous past in which Germanness and Polishness, but also ‘Silesianness’ or ‘Borderlandness’ mutually clash and dialogue. Analysis of selected exhibitions’ construction reveals peculiarities of different local contexts in transitional spaces and strategies of resolving creeping conflicts between ‘the Polishness’ and plural, peripheral ‘Polishnesses’. As authors argue, these case studies – instead of a static model of open memory conflict and binaries – offer dynamic models of memory, and allow to introduce the concept of memory frictions.